2017
DOI: 10.1051/sbuild/2017004
|View full text |Cite
|
Sign up to set email alerts
|

Carbonated miscanthus mineralized aggregates for reducing environmental impact of lightweight concrete blocks

Abstract: Abstract. At a time when the cement industry is largely responsible for the production of CO 2 in the construction sector, it is useful to make this production a reverse phenomenon: that is CO 2 capture. The CO 2 absorption process called carbonation, improves specific properties of the concrete during the conversion of carbon dioxide CO 2 into calcium carbonate CaCO 3 . Current environmental concerns motivate the study of carbonation in order to maximize the absorption of carbon dioxide. Moreover, lightweight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Lightweight aggregate concrete (LWAC) has observable benefits, including the reduction of early age shrinkage because of the internal curing effect, 1,2 reduction in dead loads implying savings in foundations and reinforcement, 3,4 improvements of thermal insulation properties, 5 enhancement of fire resistance, 6 cost savings from transportation of precast units on site, 7 and reduction in formwork and propping. 8 As a result, LWAC has a great potential to be used in many places, such as lightweight bridge decks, 9,10 lightweight structures, 11,12 lightweight foamed concrete, 13,14 lightweight concrete blocks, 15,16 or thermal isolation constructions. 17,18 Although the noteworthy benefits promise the potential application possibility of LWAC in above-mentioned areas, the bottleneck problem, namely the conflict between the density and the strength, stiffness, toughness, is always the greatest challenge of the wide applications of LWAC in fields, because of the low strength and stiffness of the lightweight aggregates and the weak bonding strength between the cement paste and the lightweight aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Lightweight aggregate concrete (LWAC) has observable benefits, including the reduction of early age shrinkage because of the internal curing effect, 1,2 reduction in dead loads implying savings in foundations and reinforcement, 3,4 improvements of thermal insulation properties, 5 enhancement of fire resistance, 6 cost savings from transportation of precast units on site, 7 and reduction in formwork and propping. 8 As a result, LWAC has a great potential to be used in many places, such as lightweight bridge decks, 9,10 lightweight structures, 11,12 lightweight foamed concrete, 13,14 lightweight concrete blocks, 15,16 or thermal isolation constructions. 17,18 Although the noteworthy benefits promise the potential application possibility of LWAC in above-mentioned areas, the bottleneck problem, namely the conflict between the density and the strength, stiffness, toughness, is always the greatest challenge of the wide applications of LWAC in fields, because of the low strength and stiffness of the lightweight aggregates and the weak bonding strength between the cement paste and the lightweight aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of Miscanthus-based lightweight concrete have been reported (Chen et al, 2017(Chen et al, , 2020Ezechiels, 2017;Waldmann et al, 2016). In addition to producing a lower density concrete, formulations have been developed that have attractive acoustic absorption properties (Chen et al, 2017) and improved environmental impact (Courard & Parmentier, 2017). Typical densities are in the range of 0.65-1.25 Mg m −3 .…”
Section: Composites Building Materials Cementmentioning
confidence: 99%
“…Because soil contamination and eventual subsequent contamination of water resources may also negatively affect the health of the ecosystem and inhabitants of the area, this process of phytoremediation contributes also to public health improvement. All of these positive effects, together with the possibility of using biomass directly for energy production; for processing into biofuels [7,41]; or as a material for other products, like paper [42] or building materials [43], can contribute to the successful reclamation of former military sites. Because phytoremediation is a low-cost method of soil restoration, it can also be used in developing countries, and Mxg biomass production can support local economic and energy independence.…”
Section: Implications For Sustainable Developmentmentioning
confidence: 99%